Epidemiology of Slipped Capital Femoral Epiphysis in Ontario, Canada. Issue 3 (March 2019) - Ravinsky, Robert; Rofaiel, James; Escott, Benjamin G.; Lim, Zachary; Ravi, Bheeshma; Howard, Andrew
Abstract : Background: Slipped capital femoral epiphysis (SCFE) is a well-characterized disorder of the hip seen in adolescent patients. It is characterized by deformity secondary to failure through the proximal femoral growth plate, which results in posterior-inferior displacement of the epiphysis on the proximal femoral metaphysis. Long-term sequelae of SCFE may include osteonecrosis, residual deformity, leg length discrepancy, degenerative joint disease, and chronic pain. The long-term consequences of SCFE may be the source of significant morbidity for the patient, and depending of the local incidence of this condition, may represent a significant expenditure of health care resources. Historically, the true incidence of SCFE within Ontario has been approximated using US-based studies of arguably comparable patient populations. In our study, we aimed to characterize the epidemiology of SCFE in the province of Ontario. Methods: We used a prospectively collected, not-for-profit Ontario research database to identify recorded cases of SCFE between April 1, 2002 and March 31, 2011. Specifically, we identified all hospital discharges with an ICD-9 or 10 diagnostic codes for SCFE in the Canadian Institute for Health Information Discharge Abstract database. Results: Over the 10-year study period, there were 648 cases of SCFE with an average annual incidence rate of 5.68/100, 000 in Ontario. Conclusions: We have observed a trend toward decreasing incidence rates of SCFE in Ontario over the last 10 years. The determination for the underlying causes for the changing trends of SCFE may be relevant for initiating public health campaigns directed at reducing the incidence of SCFE Level of Evidence: Level IV—epidemiological study.